Test the Activity of the Juice and Infusion of Rumput Kebar (Biophytum petersianum Klotzsch) againts Ascaridia galli worms in Vitro - Isti widayati; Dwi Nurhayati; Alnita Baaka (Jurnal Sain Veteriner, 2021)
Kebar grass contains active compounds that can be used as herbal ingredients in the treatment of diseases. This study was conducted to test the anthelmintic activity of grass kebar against worms Ascaridia galli in vitro. This study uses Kebar grass juice and infusion with a concentration of 15%, 30%, 45%, and 60%, and 4 repetitions. Each level of the experiment is placed in each cup containing 25 ml of solution and 5 worms. Worm mortality is recorded every 2 hours. The results showed that the juice and infusion of kebar grass were concentrations of 15%, 30%, 45%, 60% capable of killing worms with a mean time on the juice of Kebar grass respectively 9.5; 8; 7.5; 7 hours, and the average time for Kebar grass infusion is 9.5; 8.5; 8; 7.5 hours. The immersion time is a good variable to explain the variable of worm death at each concentration of treatment. There is an anthelmintic effect on grass juice and infuse kebar grass against worms Ascaridia galli in vitro. The duration of soaking and the concentration of juice and infusion of Kebar grass in this study had a significant effect on the mortality of worms. It was concluded that the juice and grass infuse kebar(Biophytum Petersianum Klotzsch) have anthelmintic effect against worms Ascaridia galli in vitro. Concentration Kebar grass juice and infuse kebar is increasing, then the shorter the time it takes to kill the worms Ascaridia galli in vitro.